Resampling methods for nonparametric regression - Mammen, Enno (Smoothing and regression, 2012)
This chapter contains sections titled: Introduction, The Idea of Bootstrap, Bootstrap in Nonparametric Regression, Bootstrap Confidence Intervals and Bands, Bootstrap-Bandwidth Choice, Bootstrap Tests in Nonparametrics, Bootstrap Inference on the Shape of a Curve, Extensions